Migration of The People of Ñuñungayocc, of the District of Palca-Huancavelica - Enciso Huamani, Edith (2021)
Migration is a social phenomenon originated by material circumstances and conditions, which is why in this article we will discuss the factors that will cause the migration of the residents of the annex of Ñuñungayocc, from the Palca district of Huancavelica city. As a methodology, the sample is recognized with the term of unit of analysis, however, in the sample, four people and their parents have been determined who contributed to obtaining the results through hermeneutic triangulation. The conclusions establish that migration was determined by the economic factor.